(untitled) (Ameghiniana, 2018)
The first AMS radiocarbon dates from the Camet Norte fossil site (Buenos Aires Province, Argentina) range from ca. 28,700 cal. BP to 27,500 cal. BP. The age of the site fits well with results of previous studies, but the more precise AMS radiocarbon dating allowed for a better determination of the site chronology, deposition and faunal attribution. It can be argued that the depositional environment of the site was not in proximity to the shoreline at the time of deposition based on palaeocoastline studies and the dates produced by this study.